THE ASYMMETRIC DRIFT AND THE ROTATION CURVE OF THE GALAXY - Golubov, O. (Одеські астрономічні публікації, 2014)
Asymmetric drift in the solar neighbourhood is studied by the means of the RAVE data. The asymmetric drift correction is applied to the SDSS data to measure the rotation curve of the Milky Way in the extended solar neighbourhood. The rotation curve is flat between7 and 10 kpc. Via fitting this flat rotation curve, and the inner rotation curve determined through tangent point method, density model of the Milky Way is constructed.